Growth of CdO films from CdO2 films by chemical bath deposition: Influence of the concentration of cadmium precursor (Superficies y Vacío, 2015)
Cadmium peroxide films were grown by chemical bath deposition on glass slides at 50 °C using CdCl2 as cadmium source. Films were deposited at different nominal cadmium concentrations. As-grown films were annealed in air at 300 °C for obtaining cadmium oxide thin films. The structural, morphological, optical and compositional properties of CdO films were analyzed in terms of the cadmium nominal composition and the annealing effect.